ANALYSIS OF QRIS IMPLEMENTATION IN IMPROVING TRANSACTION EFFICIENCY FOR MICRO ENTERPRISES IN SIHUIK-HUIK VILLAGE, SOUTH TAPANULI - Dewi Sartika Hasibuan; Saleh Ramadi C; Abdul Gani Jamora Nasution (Adisam Publisher, 2025)
The Community Service Program (KKN) of the Faculty of Economics and Islamic Business at the State Islamic University of North Sumatra, conducted in Sihuik-huik Village, South Tapanuli, serves as a form of community empowerment focusing on digital-based economic development through the implementation of QRIS. This initiative was developed in response to low levels of digital literacy and limited technological adaptation among micro-business owners in utilizing digital systems to facilitate financial transactions. QRIS (Quick Response Code Indonesian Standard) was introduced as a payment instrument to expand market access and simplify transactions between micro enterprises and consumers. This study employs a community organization approach emphasizing active collaboration between the implementation team and micro-enterprise actors in the village. This method was chosen due to its effectiveness in fostering engagement, supporting adaptation processes, and strengthening users’ capacity to apply digital payment technology such as QRIS. The findings indicate that the community demonstrated improved understanding of digital systems and successfully began utilizing QRIS-based payment methods. Several micro-business owners have implemented QRIS in daily transactions, resulting in increased convenience and transaction efficiency for both consumers and business operators. Overall, the program successfully enhanced digital payment awareness and contributed to the adoption of QRIS-based transactions among micro-enterprises.